ATELOGLUTUS ALDRICH, 1934 (DIPTERA: TACHINIDAE: VORIINI) WITH A NEW SPECIES FOR ARGENTINA (Acta Entomológica Chilena, 2022)
The description of the male sex of the Chilean-Argentinian species Ateloglutus blanchardi Cortés, 1979 isprovided in this paper, as well as a revisión of the published papers on the genus, its taxonomir situalionand its distribution in Chile, Peni and Argentina. An up-to-date kev to the six known species withreference lo the recorded host of two of them is also included, while the Chilean-Peruvian species A.velarán Cortés & Valencia, 1972, it is added to the fauna of Argentina.
Keywords: Ateloglutus blanchardi, Tachinidae, Voriini, distribution, hosts